Cytokinesis arrest and multiple centrosomes in B cell chronic lymphocytic leukaemia. Issue 5 (7th March 2018) - Rogne, Marie; Svaerd, Oksana; Madsen‐Østerbye, Julia; Hashim, Adnan; Tjønnfjord, Geir E.; Staerk, Judith
Abstract: Cytokinesis failure leads to the emergence of tetraploid cells and multiple centrosomes. Chronic lymphocytic leukaemia (CLL) is the most common haematological malignancy in adults and is characterized by clonal B cell expansion. Here, we show that a significant number of peripheral blood CLL cells are arrested in cytokinesis and that this event occurred after nuclear envelope reformation and before cytoplasmic abscission. mRNA expression data showed that several genes known to be crucial for cell cycle regulation, checkpoint and centromere function, such as ING4, ING5, CDKN1A and CDK4, were significantly dysregulated in CLL samples. Our results demonstrate that CLL cells exhibit difficulties in completing mitosis, which is different from but may, at least in part, explain the previously reported accumulation of CLL cells in G0/1.